New Frontiers in Artificial Intelligence JSAI-isAI 2011 Workshops, LENLS, JURISIN, ALSIP, MiMI, Takamatsu, Japan, December 1-2, 2011. Revised Selected Papers - Okumura, Manabu; Bekki, Daisuke; Satoh, Ken.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-proceedings of four workshops held as satellite events of the JSAI International Symposia on Artificial Intelligence 2011, in Takamatsu, Japan, in December 2011. The 25 revised full papers presented were carefully reviewed and selected from numerous papers. The papers are organized in four sections according to the four workshops: Logic and Engineering of Natural Language Semantics (LENLS), Juris-Informatics (JURISIN), Algorithms for Large-Scale Information Processing in Knowledge Discovery (ALSIP), and Multimodality in Multispace Interaction (MiMI).
Logic and Engineering of Natural Language Semantics (LENLS) -- Juris-Informatics (JURISIN) -- Algorithms for Large-Scale Information Processing in Knowledge Discovery (ALSIP) -- and Multimodality in Multispace Interaction (MiMI).
Keywords: Computer science; Data mining; Information storage and retrieval systems; Artificial intelligence; Information systems; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Mathematical Logic and Formal Languages; Computer Appl. in Administrative Data Processing